It's time to make the profession of health about health. Issue 1 (February 2013) - Becker, Craig M.; Rhynders, Patricia
Most professional health publications and presentations are not about health, but about how to avoid, prevent, or treat disease or infirmity. Better health cannot be attained by simply avoiding, preventing, or treating problems. Health efforts, therefore, should be directed toward creating physical, mental, and social wellbeing. To guide these efforts, salutogenesis, a theoretical framework about the origins or creation of health, is needed to complement the traditional pathogenesis framework that focuses on the origins and causes of disease. Salutogenic strategies are necessary to help health professionals promote positive health enhancement by making their practices about health.